Descriptors for the cultivated potato - Huaman, Z.; International Board for Plant Genetic Resources; Williams, J.T.; Salhuana, W.; Vincent, L. (International Board for Plant Genetic Resources, 1977)
A list of descriptors, descriptor definitions and descriptor states, based on usage at the International Potato Collection, Peru, is presented. Descriptors for germplasm maintenance, distribution and use are listed in an appendix.